2021
DOI: 10.1111/iwj.13692
|View full text |Cite
|
Sign up to set email alerts
|

Pressure injury prevalence and incidence in acute inpatient care and related risk factors: A cross‐sectional national study

Abstract: The aim of this national cross‐sectional study was to explore the prevalence of pressure injuries and incidence of hospital‐acquired pressure injuries, and the relating factors in somatic‐specialised inpatient care in Finland. The study was conducted in 16 (out of 21) Finnish health care organisations offering specialised health care services. Data were collected in 2018 and 2019 from adult patients (N = 5902) in inpatient, emergency follow‐up, and rehabilitation units. Pressure injury prevalence (all stages/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…1 The literature reports prevalences of 9.2% in the US and Canada, 8.7% in Australia, 14.7% in Italy, and 5.76% in Portugal. 2 A multicenter study conducted in Turkey reported the prevalence of PI to be 9.5% and found that 65.1% of PIs developed in hospital settings. Inadequate nutrition, perfusion changes, diabetes mellitus, mechanical ventilation, and comorbid conditions can decrease soft tissue tolerance for pressure and accelerate PI development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The literature reports prevalences of 9.2% in the US and Canada, 8.7% in Australia, 14.7% in Italy, and 5.76% in Portugal. 2 A multicenter study conducted in Turkey reported the prevalence of PI to be 9.5% and found that 65.1% of PIs developed in hospital settings. Inadequate nutrition, perfusion changes, diabetes mellitus, mechanical ventilation, and comorbid conditions can decrease soft tissue tolerance for pressure and accelerate PI development.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure injury (PI) prevalence varies by country and by the clinical condition of the patient 1 . The literature reports prevalences of 9.2% in the US and Canada, 8.7% in Australia, 14.7% in Italy, and 5.76% in Portugal 2 . A multicenter study conducted in Turkey reported the prevalence of PI to be 9.5% and found that 65.1% of PIs developed in hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…Because pressure injuries are most commonly caused by immobility or prolonged direct pressure, there is a high incidence of pressure injury development in patients in the ICU ( 8 ). Patients who are bedridden have a 5-fold increased risk and patients who required the use of wheelchairs had a 4-fold increased risk of developing pressure injuries ( 9 ). Furthermore, medical device related pressure injuries account for approximately 35% of hospital-acquired pressure injuries (HAPI) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 An upsurge of PI incidence in aggressive ICU was observed in recent years. 6 Owing to the abysmal prognosis and curative rates, there was a diffuse thought to take a holistic preventive approach, particularly in the nursing field. 7,8 The Braden scale to predict and assess the hazards developing PIs is worldwide used in nowadays clinical settings, which was attributed to a kind of bedside nursing.…”
Section: Introductionmentioning
confidence: 99%
“…An upsurge of PI incidence in aggressive ICU was observed in recent years 6 . Owing to the abysmal prognosis and curative rates, there was a diffuse thought to take a holistic preventive approach, particularly in the nursing field 7,8 .…”
Section: Introductionmentioning
confidence: 99%